CHROMOSOME ANALYSIS OF TWO FRESHWATER PRAWNS, MACROBRACHIUM LAMARREI LAMARREI (H. MILNE EDWARDS, 1837) AND MACROBRACHIUM DAYANUM (HENDERSON, 1893) - SARKAR, INDRANI (Journal of the Inland Fisheries Society of India, 2021)
Karyological information is extremely useful for cross-breeding, chromosome engineering and taxonomical studies for shrimps and prawns. However, there has been limited literature on it due probably to the fact that crustacean chromosomes are numerous in number and small in size. In addition, most of the chromosomes are metacentric or submetacentric (Roberts, 1969) which makes them difficult to differentiate. Some relevant cytological investigations on crustaceans which have been carried out in the past are by Niiyama (1962) on crayfish, Astacus trowbridgii, Roberts (1969) on the lobster, Homarus americanas, Mittal and Dhall (1971) on the three species of freshwater decapods, Hayashi and Fujiwara (1988) on Penaeus japonicus, Murofushi and Deguchi (1990) on Decapoda Crustacean, Chavez Justo et al. (1991) on M. Rosenbergii, Xiang et al. (1994) on marine shrimps, Lakra and Kumar (1995) of two freshwater prawns, Macrobrachium idella and M. scabriculum, Kumar and Lakra (1996) on black tiger prawn P. monodon, Campos-Ramos (1997) on marine shrimp, Mukesh et al. (2000) on marine prawn Parapenaeopsis stylifera, Zhang et al. (2003) on Fenneropenaeus chinensis, Lee et al. (2004) on the mitten crabs, Eriocheir japonica and E. sinensis, Indy et al. (2010) on tropical freshwater crayfish, Procambarus llamasi, Massimiliano et al. (2010) on the Australian crayfish (decapoda: parastacidae), Mansouri et al. (2011) on P. mergniensis and Chowdhury et al. (2013) on M. villosimanus.